Serology and magnetically controlled capsule gastroscopy for opportunistic screening of high-risk events in gastric cancer development: a cross-sectional study - Yuan Yang; Mao-Yao Wen; Jin-Chen Zou; Yan Huang; Xin-Zu Chen (Frontiers in Medicine, 2026)
Background The feasibility of magnetically controlled capsule gastroscopy (MCCG) as an alternative diagnostic tool, along with a sequential serology—MCCG protocol, needs to be assessed for its effectiveness in detecting high-risk events associated with gastric cancer development. Methods Health check-up records were collected between 2019 and 2020. Asymptomatic individuals underwent MCCG and relevant serologic examinations, which included tests for pepsinogen-I (PG-I), pepsinogen-II (PG-II), gastrin-17, carcinoembryonic antigen (CEA), and carbohydrate antigen 19-9 (CA19-9). The major outcomes from MCCG included tumors and high-risk events, specifically chronic atrophic gastritis (CAG), gastric ulcer, and gastric polyps. The detection rate of MCCG was estimated, and the predictive strength of serology for MCCG findings was analyzed. Results A total of 1,432 eligible healthy individuals undergoing routine health check-ups were included. MCCG detected no tumors, but identified 114 cases with at least one high-risk event. The overall detection rate was 79.6 per 1,000 persons for all high-risk events with specific detection rates for CAG, ulcer, and polyps being 15.4, 14.7, and 55.2 per 1,000 persons, respectively. Older individuals showed significantly higher rates of high-risk events ( p < 0.001), particularly among those aged 60 years and older. In the MCCG-detected CAG outcome dataset, serum levels of PG-I and the PG-I/-II ratio were significantly lower in the CAG group. Although the serologic tests did not effectively detect all high-risk events (AUC < 0.6, SEN < 15%), they exhibited excellent specificity (SPE > 90%). However, serologic CAG had a significant association with MCCG-detected CAG (adjusted diagnostic odds ratio = 10.40, 95% CI 2.08–51.98), despite demonstrating poor diagnostic strength (AUC = 0.555, SEN = 12.5%, SPE = 98.6%, PLR = 8.85, NLR = 0.89). The other serologic tests did not show significant associations or rational interpretation with MCCG findings. Conclusion MCCG has acceptable detection rates for high-risk events associated with gastric cancer. However, as an alternative diagnostic tool, it lacks biopsy capability, which requires sequential flexible gastroscopy for suspicious lesions. Serologic CAG was significantly associated with MCCG-detected CAG and demonstrated high specificity, suggesting its potential utility in a screening algorithm. Both the screening efficacy of MCCG and the cost-effectiveness of sequential serology-MCCG protocol require further prospective investigation against an appropriate reference standard.